HUBUNGAN ANTARA KEMAMPUAN BERBICARA BAHASA INGGRIS DENGAN HASIL TOEFL PADA TARUNA SEKOLAH TINGGI ILMU PELAYARAN (STIP) JAKARTA - Akhmad Kasan Gupron (Widyariset, 2009)
The purpose of this research was to describe the correlation between speaking ability and TOEFL (Test of English as a Foreign Language) score of cadets in Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta. The research was conducted in STIP because STIP has declared to produce internationally qualified seafarers. In line with its declaration, STIP always evaluates the cadets' English proficiency by Speaking test and TOEFL (Paper-Based TOEFL) every semester Population of this research was the first year cadets, batch 50. The respondents consisted of 20 cadets every major, so there were 60 cadets altogether. The instruments used in this research were interview form and TOEFL question set. This research showed that there was low positive correlation between speaking ability and TOEFL score. The correlation coefficient was 0.276. Therefore, it can be concluded that there are other factors influence TOEFL score. They are readiness, experience, and strategy.